Pengaruh Globalisasi Terhadap Identitas Kewarganegaraan Anak Muda - Firmansyah, Denny; Hudi, Ilham; Salsabilla, Fania; Zharfa, Sabila; Rahmadani, Fitri; Fadhlurrahman, Ziyad (International Forum of Researchers and Lecturers, 2024)
Globalization has affected various aspects of modern society, one of which is the citizenship identity of young people. The influence of globalization on young people's citizenship identity is a major concern in the life of the nation today. Citizenship identity is an important thing for a citizen. Therefore, this study aims to analyze how globalization affects young people's citizenship identity. The influence of globalization can be seen in young people's lifestyle, consumption and cultural preferences. In the context of citizenship identity, globalization can challenge the clash between local and global identities, raising questions about their loyalty to their home country. The research methods used included a literature. The results of the analysis show that globalization has caused changes in young people's mindsets, values, and citizenship identities. The process of globalization has opened up young people's access to information, cultures and experiences from different parts of the world that change the way they see themselves as citizens. This research provides insights into the dynamics of citizenship identity in the era of globalization in order to promote active and responsible citizenship.